Measurement of Line Balancing in the Production Process Copper Cathode at PT. Smelting Using Ranked Positional Weight (RPW) Method - Wardana, Muhammad Donny Putra; Saifuddin, Joumil Aidil (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Line balancing is required in the production process. Without a balanced production line at work stations, the production process is less effective and efficient. Refinery at PT. Smelting has a type of mass production process, so it is planned to determine the optimal production line so that the loading on each work station will be more evenly distributed and reduce idle time. The method used is the measurement of working time with a stop watch. the data used is the work element and the time needed by the operator to complete the copper cathode production process which is from the anode arriving at the Anode Preparation Machine (APM) until the copper cathode is finished strapping at the Cathode Washing & Stripping Machine (CWSM). There are two results of the analysis,based on the first analysis that by using the line balancing method, the company can achieve a line efficiency of 78.10% and reduce the balance delay by 15.11% which is from 37.01% to 21.90%.